HOTS Based on Revised Bloom's Taxonomy : Analysis in English Examination Test Items Used in High School Level - Sausan, Kania; Rohmatillah, Rohmatillah; Rini, Yulan Puspita (Universitas Islam Negeri Raden Intan Lampung, 2023)
Today, humans must think critically to face all challenges. In order to improve Indonesia's PISA survey results, the government developed the 2013 curriculum, which emphasizes critical and creative thinking. The aims of this research were to determine the proportion of HOTS and HOTS characteristics reflected in high school English test questions. The objects of the research were the English midterm and final exams for the 10th and 11th grades in the second semester of the 2021–2022 academic year used at MAN 1 Lampung Tengah. This study used a qualitative content analysis design. The study found that in the mid-term 10 grade, there were 6 items, or 20%, labeled